THE PRINCIPLE OF MULTICULTURALISM IN QS. AL-HUJURAT (49): 13 FROM QURAISH SHIHAB’S PERSPECTIVE : (An Analysis Based on Hans-Georg Gadamer’s Hermeneutical Theory) - Mustiadi Gafar Alifandi; Ahmad Ass'ari (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
Surah al-Hujurat verse 13 contains significant multiculturalism values, emphasizing the importance of respect for human diversity as a form of mercy for all nature (rahmatan li al-alamin). This verse provides a strong theological foundation for creating a harmonious life in the midst of diversity. This study attempts to interpret the verse through the interpretation of Quraish Shihab, a contemporary mufasir known for his contextual and humanist approach, which specifically highlights the relevance of Qur'anic values to modern social dynamics. To reveal a deeper message than just the literal meaning of Surah Al-Hujurat verse 13, this study begins by outlining the basic theories of Hans-Georg Gadamer's hermeneutics. Furthermore, the theory is used as an analytical tool to understand and explore Quraish Shihab's interpretation of this verse more comprehensively. This type of study is qualitative with a literature approach. The data collection method uses documentation techniques, while the data analysis method uses a philosophical approach. The resulting meanings include emphasizing the importance of knowing each other to create social harmony, recognition of the egalitarian principle that rejects discrimination based on ethnicity, race, or social status, and emphasis on piety as a measure of glory in the sight of Allah.